Short Communication: The presence of extended-spectrum beta-lactamase (ESBL) producing Escherichia coli on layer chicken farms in Blitar Area, Indonesia - Freshinta Jellia Wibisono; BAMBANG SUMIARTO; TRI UNTARI; Mustofa Helmi Effendi; DIAN AYU PERMATASARI; ADIANA MUTAMSARI WITANINGRUM (Society for Indonesian Biodiversity, 2020)
Abstract. Wibisono FJ, Sumiarto B, Untari T, Effendi MH, Permatasari DA, Witaningrum AM. 2020. Short Communication: The presence of extended-spectrum beta-lactamase (ESBL) producing Escherichia coli on layer chicken farms in Blitar Area, Indonesia. Biodiversitas 21: 2667-2671. This study was aimed to determine the incidence of Extended-Spectrum Beta-Lactamase (ESBL) producing Escherichia coli on layer chicken in Blitar area. This was a cross-sectional study with a total of 205 cloacal swabs of layer chicken taken randomly. The sample was in isolation identification on MacConkey media and ESBL confirmation test produced by Escherichia coli was then carried out by the Double Disc Synergy Test (DDST) method and the VITEK® 2 Compact Automated System method. This study showed that 185 (90.24%) isolates of positive Escherichia coli from a total of 205 samples of cloacal swabs of the layer chicken. The incidence of ESBL-producing Escherichia coli in cloacal swabs on layer chicken with the Double Disc Synergy Test (DDST) method and the VITEK® 2 compact automatic method was 13 (7.03%). Results in this study indicated that layer chicken has potential as reservoir for spreading ESBL to public health and needs strict hygienic measures to prevent their transmission to humans.